A monovalent selectively permeable anion exchange membrane with double cross-linking structure and a preparation method thereof
By adopting dual crosslinking structure and ATRP reaction technology in the monovalent selectable permeability anion exchange membrane, the existing film surface has been solved, and low resistance, high selectivity and stable film performance is achieved, suitable for Industrialized production.
Patent Information
- Application Number
- CN202411504931.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-28
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-10-28
AI Technical Summary
The existing unit price choice permeable ion exchange membrane has a high resistance to the membrane surface after the structural density is increased, and the energy consumption is large during use. After a long period of use, the ion membrane swells, the structure tends to loosen, and the ionic sieving is ionic. The effect' decreases, and the separation effect becomes worse.
The monovalent selection of permeable anion exchange membrane with a dual crosslinking structure is adopted. The base film is prepared by impregnation polymerization process from 4-vinylpyridine and para-divinylbenzene monomer, and then 1,3-dibromobenzene and the base film is used. The pyridine groups in the quaternization reaction occurs to form an anion exchange membrane, and sodium styrene sulfonate or 2-acrylamide-2-methylpropanesulfonic acid is grafted on the surface of the anion exchange membrane through ATRP reaction to form a reverse charge layer.
It realizes the characteristics of low film surface resistance, high selectivity and stability, and simplifies the preparation process, reduces the cost of film material production, and is suitable for large-scale industrial production.
Smart Images

Figure CN119034498B_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of polymer materials, and in particular to a monovalent selectively permeable anion exchange membrane with a double cross-linked structure and a preparation method thereof. Background Art
[0002] The preparation method of monovalent selective permeable ion exchange membrane mainly increases the cross-linking density of the ion exchange membrane or forms a very thin high cross-linking density resin on the surface of a low cross-linking density ion exchange membrane, which can make the permeability of monovalent ions significantly higher than that of high-valent ions. Or introducing a small amount of anion / cation exchange groups into the cation / anion exchange membrane or forming a thin layer of charged polyelectrolyte on the surface of the cation / anion exchange membrane can also increase the monovalent ion selective permeability of the membrane. Monovalent selective permeable ion exchange membranes are divided into monovalent selective permeable cation exchange membranes and monovalent selective permeable anion exchange membranes, which can respectively realize the separation between monovalent cations and multivalent cations and between monovalent anions and multivalent anions, and are widely used in the fields of lithium extraction from brine, refined crude salt, purified irrigation water, and recovery and utilization of useful components in industrial wastewater.
[0003] The preparation of monovalent selective permeable ion exchange membrane mainly includes: first, introducing functional groups with affinity for multivalent ions into the membrane to inhibit the permeation of multivalent ions; second, increasing the cross-linking degree of the membrane to make its structure denser, and reducing the permeability of multivalent ions by means of the "screening effect". However, the preparation of monovalent selective permeable ion exchange membranes by doping modification or surface modification generally has a complex manufacturing process, which is not conducive to large-scale industrial production. The ion exchange membranes that achieve monovalent selective permeability by increasing the density of the ion membrane structure and using the ion "screening effect" generally have high membrane surface resistance due to their dense structure, and consume more energy during use. After long-term use, the ion membrane swells and the structure tends to be loose, the ion "screening effect" decreases, and the separation effect becomes worse. Summary of the invention
[0004] The purpose of the present invention is to solve the shortcomings of the above-mentioned technology and provide a monovalent selective anion exchange membrane with a double cross-linked structure and a preparation method thereof. The monovalent selective anion exchange membrane has the characteristics of low membrane surface resistance, high selectivity and stability. At the same time, the preparation process operation method is simple and the membrane material production cost is low.
[0005] To this end, the present invention provides a method for preparing a monovalent selectively permeable anion exchange membrane having a double cross-linked structure, the steps of which include:
[0006] Step S1. Preparation of basement membrane solution
[0007] 4-vinylpyridine, a crosslinking agent and an initiator are used in N,N-dimethylformamide or N-methylpyrrolidone as a solvent to prepare a solution A;
[0008] Dissolve 1,3-dibromopropane in N,N-dimethylformamide or N-methylpyrrolidone to prepare solution B;
[0009] Step S2. Preparation of basement membrane
[0010] The porous support cloth is used as a substrate, and the substrate is immersed in the solution A prepared in step S1. After the substrate is fully impregnated, the substrate is taken out and sandwiched between two thin sandwich sheets so that the three are combined into one body to prepare a composite body; the prepared composite body is subjected to a polymerization reaction, and after the reaction is completed, the two thin sandwich sheets are peeled off to obtain a base film;
[0011] Step S3. Preparation of anion exchange membrane
[0012] The base membrane obtained in step S2 is immersed in the solution B obtained in step S1, so that the 1,3-dibromopropane in the solution B reacts with the pyridine groups in the base membrane to undergo a quaternization reaction, thereby obtaining an anion exchange membrane;
[0013] Step S4. Preparation of monovalent permselective anion exchange membrane
[0014] Sodium styrene sulfonate or 2-acrylamide-2-methylpropane sulfonic acid is dissolved in N,N-dimethylformamide or N-methylpyrrolidone to prepare solution C, copper bromide, ascorbic acid, and 2,2′-bipyridine are added to solution C, stirred to completely dissolve, and then the anion exchange membrane prepared in step S3 is added for soaking, so that sodium styrene sulfonate or 2-acrylamide-2-methylpropane sulfonic acid reacts with bromine groups in the surface layer of the anion exchange membrane to undergo ATRP reaction, wherein copper bromide reacts with ascorbic acid to produce cuprous bromide, and cuprous ions form a complex with 2,2′-bipyridine as a catalyst for the ATRP reaction; the entire process is carried out in an oxygen-free environment, and a monovalent selective permeable anion exchange membrane is finally obtained.
[0015] Preferably, in step S1, the molar ratio of 4-vinylpyridine, cross-linking agent and initiator is 1:0.13-0.50:0.0072-0.081.
[0016] Preferably, in step S1, the crosslinking agent is p-divinylbenzene or ethylene glycol methacrylate.
[0017] Preferably, in step S1, the initiator is one of azobisisobutyronitrile, azobisisoheptylnitrile, dibenzoyl peroxide, dodecyl peroxide, tert-butyl peroxyvalerate, diisopropyl peroxydicarbonate, and dicyclohexyl peroxydicarbonate.
[0018] Preferably, in step S1, the solute concentration of the prepared solution A is 60-80%; the solute concentration of the prepared solution B is 5-20%.
[0019] Preferably, in step S2, the porous support cloth has a pore size of 0.1-1 μm, a porosity of 45-65%, a thickness of 50-200 μm, and is made of one of polypropylene, polyvinyl chloride, nylon, and polyester.
[0020] Preferably, in step S2, there are no bubbles between the substrate of the prepared composite and the two thin sheets.
[0021] Preferably, in step S2, the polymerization reaction temperature is 80-100°C.
[0022] Preferably, in step S4, the solute concentration of the prepared solution C is 0.5-2%.
[0023] Preferably, in step S4, the ATRP reaction temperature is 60-80°C.
[0024] Preferably, in step S4, a large amount of nitrogen is continuously introduced into solution C during the process of preparing solution C and adding copper bromide, 2,2′-bipyridine and ascorbic acid to solution C until they are dissolved, so as to discharge the oxygen dissolved in the solution; the anion exchange membrane prepared in step S3 is added for immersion, and the membrane is sealed to isolate the air to ensure that the entire process is carried out in an oxygen-free environment.
[0025] Preferably, the monovalent selectively permeable anion exchange membrane with a double cross-linked structure prepared by the above method is provided with a porous support cloth, the pores of the porous support cloth are filled with charged polymers, the charged polymers have a cross-linked structure, and a semi-interpenetrating network structure is formed between the polymer chains and the porous support cloth; the charged groups of the charged polymers are distributed in three layers, wherein the ion exchange groups of the middle main layer are pyridine-type positively charged groups, and the ion exchange groups of the surface layers on both sides are sulfonate-type negatively charged groups.
[0026] The beneficial effects of the present invention are as follows: the present invention provides a monovalent selectively permeable anion exchange membrane with a double cross-linked structure and a preparation method thereof, which has the characteristics of low membrane surface resistance, high selectivity and stability, and at the same time, the preparation process operation method is simple, the membrane material production cost is low, and it is suitable for large-scale industrial production.
[0027] (1) A base membrane with a semi-interpenetrating network structure is prepared by using 4-vinylpyridine and p-divinylbenzene monomers through an impregnation polymerization process. Then, 1,3-dibromopropane is used to react with the pyridine groups in the base membrane to undergo a quaternization reaction to prepare an anion exchange membrane containing -Br active groups. Finally, sodium styrene sulfonate or 2-acrylamido-2-methylpropane sulfonic acid is grafted onto the surface of the anion exchange membrane through an ATRP reaction to form a countercharge layer on the surface of the anion exchange membrane, thereby preparing an anion exchange membrane with monovalent selectivity.
[0028] (2) The prepared monovalent selectively permeable anion exchange membrane has a porous support cloth whose pores are filled with charged polymers. The charged polymers have a cross-linked structure, and a semi-interpenetrating network structure is formed between the polymer chains and the porous support cloth. The charged groups of the charged polymers are distributed in three layers, wherein the ion exchange groups of the middle main layer are pyridine-type positively charged groups, which have high anion conductivity and ensure high permeability of monovalent anions; the ion exchange groups of the two side surface layers are sulfonate-type negatively charged groups, which have the property of repelling multivalent anions and ensure high selectivity of monovalent ions. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application.
[0030] Figure 1 The figures are scanning electron microscope images, among which (a) is a cross-sectional electron microscope image of a porous support cloth; (b) is a surface electron microscope image of a porous support cloth; (c) is a cross-sectional electron microscope image of a monovalent selective anion exchange membrane; (d) is a surface electron microscope image of a monovalent selective anion exchange membrane;
[0031] Figure 2 Schematic diagram of the charged polymer of the present invention. DETAILED DESCRIPTION
[0032] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present application clearer, the present application is further described in detail in conjunction with the embodiments below. It should be understood that the specific embodiments described herein are only used to explain the present application and are not used to limit the present application. The methods used in the present invention are conventional methods unless otherwise specified; the raw materials and devices used are conventional commercial products unless otherwise specified.
[0033] Embodiment 1:
[0034] (1) Preparation of basement membrane solution
[0035] Weigh 8.67 g of 4-vinylpyridine, 2.60 g of p-divinylbenzene and 0.11 g of azobisisobutyronitrile, add 4.83 g of solvent N-methylpyrrolidone, stir and dissolve to prepare solution A. Then weigh 10 g of 1,3-dibromopropane, add 190 g of solvent N-methylpyrrolidone, stir and dissolve to prepare solution B.
[0036] The molar ratio of 4-vinylpyridine, p-divinylbenzene and azobisisobutyronitrile is 1:0.24:0.081; the solute concentration of solution A is 70%, and the solute concentration of solution B is 5%.
[0037] (2) Preparation of basement membrane
[0038] A porous support cloth made of polypropylene (PP) with a pore size of 1 μm, a porosity of 65% and a thickness of 200 μm is used as the substrate. The substrate is immersed in the solution A prepared in step (1). After the substrate is fully impregnated, the substrate is taken out and sandwiched between two thin PET sandwich sheets to make the three composited into one. There should be no bubbles between the substrate and the two thin sandwich sheets. The obtained composite is then heated at 80°C for 12 hours. After the two thin sandwich sheets are peeled off, the base film is obtained.
[0039] (3) Preparation of anion exchange membrane
[0040] The base membrane prepared in step (2) is immersed in solution B prepared in step (1) at room temperature for 24 hours to obtain an anion exchange membrane.
[0041] (4) Preparation of monovalent permselective anion exchange membrane
[0042] Weigh 0.75g of sodium styrene sulfonate and dissolve it in 145g of solvent N-methylpyrrolidone to prepare solution C (solute concentration is 0.5%); and continue to pass a large amount of nitrogen into solution C for 1 hour to discharge the oxygen dissolved in solution C. Then add 0.011g of copper bromide, 0.016g of 2,2′-bipyridine, and 0.089g of ascorbic acid to solution C, stir to completely dissolve, and continue to pass nitrogen. Finally, immerse the anion exchange membrane prepared in step 3 in the solution, seal it to isolate it from air, and place it at 60°C for reaction for 24 hours to obtain a monovalent selective permeable anion exchange membrane.
[0043] (5) Performance testing
[0044] The membrane surface resistance of the sample and the separation factor of chloride ion / sulfate ion in 0.5 mol / L sodium chloride aqueous solution and 0.5 mol / L sodium sulfate aqueous solution were tested. The test results are shown in Table 1 below.
[0045] Table 1 Test results of membrane surface resistance and separation factor of sample in Example 1
[0046]
[0047] The test results show that in a 0.5 mol / L aqueous solution of NaCl, the membrane surface resistance of the anion exchange membrane is 7.0-7.9 Ω·cm 2 In a 0.5 mol / L aqueous solution of Na2SO4, the membrane surface resistance of the anion exchange membrane is 51-58 Ω·cm 2 , separation factor (Cl - / SO4 2- ) is 3.1-3.7, indicating that the anion exchange membrane has a lower membrane surface resistance (in NaCl solution) and a higher separation factor (Cl - / SO4 2- ).
[0048] Embodiment 2:
[0049] (1) Preparation of basement membrane solution
[0050] Weigh 9.76 g of 4-vinylpyridine, 1.63 g of p-divinylbenzene and 0.11 g of azobisisobutyronitrile, add 6.05 g of solvent N-methylpyrrolidone, stir and dissolve to prepare solution A. Then weigh 10 g of 1,3-dibromopropane, add 90 g of solvent N-methylpyrrolidone, stir and dissolve to prepare solution B.
[0051] The molar ratio of 4-vinylpyridine, p-divinylbenzene and azobisisobutyronitrile is 1:0.13:0.0072; the solute concentration of solution A is 66%, and the solute concentration of solution B is 10%.
[0052] (2) Preparation of basement membrane
[0053] A PP porous support cloth with a pore size of 0.1 μm, a porosity of 45%, and a thickness of 50 μm is used as the substrate. The substrate is immersed in the solution A prepared in step (1). After being fully impregnated, the substrate is taken out and sandwiched between two PET thin sheets to make the three of them composited into one. There should be no bubbles between the substrate and the two thin sheets. The obtained composite is then heated at 80°C for 12 hours. After peeling off the two thin sheets, the base film is obtained.
[0054] (3) Preparation of anion exchange membrane
[0055] The base membrane prepared in step (2) is immersed in solution B prepared in step (1) at room temperature for 24 hours to obtain an anion exchange membrane.
[0056] (4) Preparation of monovalent permselective anion exchange membrane
[0057] Weigh 0.75g of 2-acrylamido-2-methylpropanesulfonic acid and dissolve it in 90g of solvent N-methylpyrrolidone to prepare solution C (solute concentration is 0.8%); and continue to pass a large amount of nitrogen into solution C for 1 hour to discharge the oxygen dissolved in solution C. Then add 0.011g of copper bromide, 0.016g of 2,2′-bipyridine, and 0.089g of ascorbic acid to solution C, stir to completely dissolve, and continue to pass nitrogen. Finally, immerse the anion exchange membrane prepared in step 3 in the solution, seal it to isolate it from air, and place it at 65°C for reaction for 24 hours to obtain a monovalent selective permeable anion exchange membrane.
[0058] (5) Performance testing
[0059] The membrane surface resistance of the sample and the separation factor of chloride ion / sulfate ion in 0.5 mol / L sodium chloride aqueous solution and 0.5 mol / L sodium sulfate aqueous solution were tested. The test results are shown in Table 2 below.
[0060] Table 2 Test results of membrane surface resistance and separation factor of sample in Example 2
[0061]
[0062] The test results show that in a 0.5 mol / L NaCl aqueous solution, the membrane surface resistance of the anion exchange membrane is 7.7-8.7 Ω·cm 2 In a 0.5 mol / L aqueous solution of Na2SO4, the membrane surface resistance of the anion exchange membrane is 34-42 Ω·cm 2 , separation factor (Cl - / SO4 2- ) is 3.1-3.3, indicating that the anion exchange membrane has a lower membrane surface resistance (in NaCl solution) and a higher separation factor (Cl - / SO4 2- ).
[0063] Embodiment 3:
[0064] (1) Preparation of basement membrane solution
[0065] Weigh 10.52 g of 4-vinylpyridine, 6.51 g of p-divinylbenzene and 0.25 g of azobisisobutyronitrile, add 11.4 g of solvent N-methylpyrrolidone, stir and dissolve to prepare solution A. Then weigh 15 g of 1,3-dibromopropane, add 85 g of solvent N-methylpyrrolidone, stir and dissolve to prepare solution B.
[0066] The molar ratio of 4-vinylpyridine, p-divinylbenzene and azobisisobutyronitrile is 1:0.50:0.0152; the solute concentration of solution A is 60%, and the solute concentration of solution B is 15%.
[0067] (2) Preparation of basement membrane
[0068] A PP porous support cloth with a pore size of 0.1 μm, a porosity of 58%, and a thickness of 70 μm is used as the substrate. The substrate is immersed in the solution A prepared in step (1). After being fully impregnated, the substrate is taken out and sandwiched between two PET thin sheets to make the three of them composited into one. There should be no bubbles between the substrate and the two thin sheets. The obtained composite is then heated at 90°C for 6 hours. After peeling off the two thin sheets, a base film is obtained.
[0069] (3) Preparation of anion exchange membrane
[0070] The base membrane prepared in step (2) is immersed in solution B prepared in step (1) at room temperature for 24 hours to obtain an anion exchange membrane.
[0071] (4) Preparation of monovalent permselective anion exchange membrane
[0072] Weigh 0.75g of sodium styrene sulfonate and dissolve it in 60g of solvent N-methylpyrrolidone to prepare solution C (solute concentration is 1.2%); then continue to pass a large amount of nitrogen into solution C for 1 hour to discharge the oxygen dissolved in solution C. Then add 0.011g of copper bromide, 0.016g of 2,2′-bipyridine, and 0.089g of ascorbic acid to solution C, stir to completely dissolve, and continue to pass nitrogen. Finally, immerse the anion exchange membrane prepared in step 3 in the solution, seal it to isolate it from air, and place it at 70°C for reaction for 24 hours to obtain a monovalent selective permeable anion exchange membrane.
[0073] (5) Performance testing
[0074] The membrane surface resistance of the sample and the separation factor of chloride ion / sulfate ion in 0.5 mol / L sodium chloride aqueous solution and 0.5 mol / L sodium sulfate aqueous solution were tested. The test results are shown in Table 3 below.
[0075] Table 3 Test results of membrane surface resistance and separation factor of samples in Example 3
[0076]
[0077] The test results show that in a 0.5 mol / L NaCl aqueous solution, the membrane surface resistance of the anion exchange membrane is 14-17 Ω·cm 2In a 0.5 mol / L aqueous solution of Na2SO4, the membrane surface resistance of the anion exchange membrane is 72 to 96 Ω·cm 2 , separation factor (Cl - / SO4 2- ) is 3.8-4.3, indicating that the electrochemical properties of the ion exchange membrane, such as resistance and separation factor, can be precisely controlled by increasing the amount of cross-linking agent and improving the cross-linking degree of the anion exchange membrane main layer.
[0078] Embodiment 4:
[0079] (1) Preparation of basement membrane solution
[0080] Weigh 9.76 g of 4-vinylpyridine, 3.04 g of p-divinylbenzene and 0.17 g of azobisisobutyronitrile, add 3.3 g of solvent N-methylpyrrolidone, stir and dissolve to prepare solution A. Then weigh 10 g of 1,3-dibromopropane, add 40 g of solvent N-methylpyrrolidone, stir and dissolve to prepare solution B.
[0081] The molar ratio of 4-vinylpyridine, p-divinylbenzene and azobisisobutyronitrile is 1:0.25:0.0112; the solute concentration of solution A is 80%, and the solute concentration of solution B is 20%.
[0082] (2) Preparation of basement membrane
[0083] A PP porous support cloth with a pore size of 0.2 μm, a porosity of 58%, and a thickness of 70 μm is used as the substrate. The substrate is immersed in the solution A prepared in step (1). After being fully impregnated, the substrate is taken out and sandwiched between two PET thin sheets to make the three of them composited into one. There should be no bubbles between the substrate and the two thin sheets. The obtained composite is then heated at 100° C. for 6 hours. After peeling off the two thin sheets, a base film is obtained.
[0084] (3) Preparation of anion exchange membrane
[0085] The base membrane prepared in step (2) is immersed in solution B prepared in step (1) at room temperature for 24 hours to obtain an anion exchange membrane.
[0086] (4) Preparation of monovalent permselective anion exchange membrane
[0087] Weigh 0.75g of 2-acrylamido-2-methylpropanesulfonic acid and dissolve it in 38g of solvent N-methylpyrrolidone to prepare solution C (solute concentration is 2%); then continue to pass a large amount of nitrogen into solution C for 1 hour to discharge the oxygen dissolved in solution C. Then add 0.011g of copper bromide, 0.016g of 2,2′-bipyridine, and 0.089g of ascorbic acid to solution C, stir to completely dissolve it, and continue to pass nitrogen. Finally, immerse the anion exchange membrane prepared in step 3 in the solution, seal it to isolate it from the air, and place it at 80°C for reaction for 24 hours to obtain a monovalent selective anion exchange membrane.
[0088] (5) Performance testing
[0089] The membrane surface resistance of the sample and the separation factor of chloride ion / sulfate ion in 0.5 mol / L sodium chloride aqueous solution and 0.5 mol / L sodium sulfate aqueous solution were tested. The test results are shown in Table 4 below.
[0090] Table 4 Test results of membrane surface resistance and separation factor of samples in Example 4
[0091]
[0092] The test results show that in a 0.5 mol / L NaCl aqueous solution, the membrane surface resistance of the anion exchange membrane is 9.7-11.3 Ω·cm 2 In a 0.5 mol / L aqueous solution of Na2SO4, the membrane surface resistance of the anion exchange membrane is 41-47 Ω·cm 2 , separation factor (Cl - / SO4 2- ) is 3.5~3.8.
[0093] The porous support fabrics used in the preparation process of Examples 1 to 4 were examined by scanning electron microscopy. Figure 1 As shown, Figure 1 (a) and (b) are cross-sectional electron microscopy images and surface electron microscopy images of the porous support cloth, respectively. As shown in Figure (a), the porous support cloth is honeycomb-shaped with a large number of void structures; as shown in Figure (b), there are a large number of needle-shaped circular holes on the surface of the porous support cloth, which are connected to the internal voids.
[0094] The monovalent selective anion exchange membrane prepared in Example 1 was examined by scanning electron microscopy. Figure 1 As shown, Figure 1(c) and (d) are cross-sectional electron micrographs and surface electron micrographs of the monovalent permselective anion exchange membrane, respectively. As shown in Figure (c), the anion exchange membrane is filled with charged polymers and has no voids. As shown in Figure (d), the surface of the anion exchange membrane is filled with charged polymers and has no holes, and is smooth and dense.
[0095] The monovalent selective permeable anion exchange membrane prepared by the present invention is provided with a porous support cloth, the pores of the porous support cloth are filled with charged polymers, the charged polymers have a cross-linked structure, and a semi-interpenetrating network structure is formed between the polymer chains and the porous support cloth; Figure 2 As shown, the charged groups of the charged polymer are distributed in three layers, in which the ion exchange groups of the middle main layer are pyridine-type positively charged groups, which have high anion conductivity and ensure high permeability of monovalent anions; the ion exchange groups of the two side surface layers are sulfonate-type negatively charged groups, which have the property of repelling multivalent anions and ensure high selectivity of monovalent ions.
[0096] The main layer of the charged polymer has high conductivity, and its ion exchange group is a pyridine-type positively charged group. Through the in-situ polymerization of a mixed solution of 4-vinylpyridine and p-divinylbenzene in a porous support cloth, and then the quaternization reaction of 1,3-dibromopropane and pyridine groups, a functional polymer with a positively charged group and a double cross-linked structure is formed. The polymer chains of the functional polymer are interpenetrated and entangled to form a semi-interpenetrating network structure with the porous support cloth, that is, an anion exchange membrane is obtained. The semi-interpenetrating network structure improves the stability and service life of the main layer.
[0097] The ion exchange groups on both sides of the charged polymer surface are sulfonate-type negatively charged groups. Through the ATRP reaction between sodium styrene sulfonate or 2-acrylamide-2-methylpropane sulfonic acid and the bromine groups on the polymer chains of the functional polymer of the prepared anion exchange membrane, negatively charged sulfonic acid groups are introduced into the two sides of the surface of the anion exchange membrane, thereby forming a three-layer distribution structure; the polymer molecular chains on the two sides of the surface are respectively entangled with the molecular chains of the main layer and are integrated with each other, thereby improving the stability of the monovalent anion selective permeability of the anion exchange membrane.
[0098] The present invention provides a monovalent selective permeable anion exchange membrane with a double cross-linked structure, which has the characteristics of low membrane surface resistance, high selectivity and stability. The main layer uses functional monomers and cross-linking agents in the pores of a porous support cloth to prepare an anion exchange membrane with a semi-interpenetrating network structure by in-situ polymerization. By adjusting the types and proportions of functional monomers and cross-linking agents, the performance indicators such as the membrane surface resistance and ion migration number of the main layer ion exchange membrane can be accurately controlled. At the same time, using the ATRP reaction, negatively charged sulfonic acid groups are introduced into the surface layer of the anion exchange membrane, and electrostatic repulsion is used to prevent high-valent anions from passing through the ion membrane, thereby achieving selective permeability separation of monovalent ions.
[0099] The present invention also provides a method for preparing a monovalent selective permeable anion exchange membrane with a double cross-linked structure, which has a simple process operation method, low membrane material production cost, and is suitable for large-scale industrial production. 4-vinylpyridine and p-divinylbenzene are copolymerized to form a polymer material with a CC structure as the main chain, with pyridine groups connected to the main chain, and a cross-linked structure is formed between different polymer main chains through p-divinylbenzene; 1,3-dibromopropane is reacted with pyridine groups to form positively charged functional groups, and part of 1,3-dibromopropane can react with pyridine groups on different molecular chains to form a cross-linked structure; sodium p-vinylbenzene sulfonate or 2-acrylamide-2-methylpropane sulfonic acid is used to react with the bromine groups in the surface positively charged functional groups of the membrane material to generate ATRP reaction to introduce negatively charged groups. The membrane material has a double cross-linked structure, with the main body being rich in positively charged pyridine groups and the surface being a small amount of negatively charged sulfonic acid groups.
[0100] In the above embodiments 1 to 4, it should be noted that:
[0101] (1) In addition to azobisisobutyronitrile, the initiator may also be azobisisoheptylnitrile, dibenzoyl peroxide, dodecyl peroxide, tert-butyl peroxyvalerate, diisopropyl peroxydicarbonate, dicyclohexyl peroxydicarbonate, or the like.
[0102] (2) The crosslinking agent may be p-divinylbenzene or other crosslinking agents such as ethylene glycol methacrylate.
[0103] (3) The solvent may be N-methylpyrrolidone or N,N-dimethylformamide.
[0104] (4) The porous support cloth may be made of other materials besides polypropylene, such as polyvinyl chloride, nylon, and polyester.
[0105] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present application should be included in the protection scope of the present application.
Claims
1. A method for preparing a monovalent selectively permeable anion exchange membrane having a double cross-linked structure, characterized in that: The steps include: Step S1. Preparation of basement membrane solution, 4-vinylpyridine, a crosslinking agent and an initiator are used in N,N-dimethylformamide or N-methylpyrrolidone as a solvent to prepare a solution A; the crosslinking agent is p-divinylbenzene or ethylene glycol methacrylate; Dissolve 1,3-dibromopropane in N,N-dimethylformamide or N-methylpyrrolidone to prepare solution B; Step S2. Preparation of basement membrane, The porous support cloth is used as a substrate, and the substrate is immersed in the solution A prepared in step S1. After the substrate is fully impregnated, the substrate is taken out and sandwiched between two thin sandwich sheets so that the three are combined into one body to prepare a composite body; the prepared composite body is subjected to a polymerization reaction, and after the reaction is completed, the two thin sandwich sheets are peeled off to obtain a base film; Step S3. Preparation of anion exchange membrane, The base membrane obtained in step S2 is immersed in the solution B obtained in step S1, so that the 1,3-dibromopropane in the solution B reacts with the pyridine groups in the base membrane to undergo a quaternization reaction, thereby obtaining an anion exchange membrane; Step S4. Preparation of a monovalent selectively permeable anion exchange membrane, Sodium styrene sulfonate or 2-acrylamide-2-methylpropane sulfonic acid is dissolved in N,N-dimethylformamide or N-methylpyrrolidone to prepare solution C; copper bromide, ascorbic acid, and 2,2′-bipyridine are added to solution C, stirred to completely dissolve, and then the anion exchange membrane prepared in step S3 is added to soak, so that sodium styrene sulfonate or 2-acrylamide-2-methylpropane sulfonic acid reacts with bromine groups in the surface layer of the anion exchange membrane by ATRP. The whole process is carried out in an oxygen-free environment, and finally a monovalent selective permeable anion exchange membrane is prepared.
2. The method for preparing a monovalent selectively permeable anion exchange membrane having a double cross-linked structure according to claim 1, characterized in that: In step S1, the molar ratio of 4-vinylpyridine, cross-linking agent and initiator is 1:0.13-0.50:0.0072-0.
081.
3. The method for preparing a monovalent selectively permeable anion exchange membrane having a double cross-linked structure according to claim 1, characterized in that: In step S1, the initiator is one of azobisisobutyronitrile, azobisisoheptylnitrile, dibenzoyl peroxide, dodecyl peroxide, tert-butyl peroxyvalerate, diisopropyl peroxydicarbonate, and dicyclohexyl peroxydicarbonate.
4. The method for preparing a monovalent selectively permeable anion exchange membrane having a double cross-linked structure according to claim 1, characterized in that: In step S1, the solute mass concentration of the prepared solution A is 60-80%; the solute mass concentration of the prepared solution B is 5-20%.
5. The method for preparing a monovalent selectively permeable anion exchange membrane having a double cross-linked structure according to claim 1, characterized in that: In step S2, the porous support cloth has a pore size of 0.1-1 μm, a porosity of 45-65%, a thickness of 50-200 μm, and is made of one of polypropylene, polyvinyl chloride, nylon, and polyester.
6. The method for preparing a monovalent selectively permeable anion exchange membrane having a double cross-linked structure according to claim 1, characterized in that: In step S2, the polymerization reaction temperature is 80-100°C.
7. The method for preparing a monovalent selectively permeable anion exchange membrane having a double cross-linked structure according to claim 1, characterized in that: In step S4, the solute mass concentration of the prepared solution C is 0.5-2%.
8. The method for preparing a monovalent selectively permeable anion exchange membrane having a double cross-linked structure according to claim 1, characterized in that: In step S4, the ATRP reaction temperature is 60-80°C.
9. A monovalent selectively permeable anion exchange membrane having a double cross-linked structure prepared by the method according to any one of claims 1 to 8, characterized in that: It is provided with the porous support cloth, the pores of the porous support cloth are filled with charged polymers, the charged polymers have a cross-linked structure, and a semi-interpenetrating network structure is formed between the polymer chains and the porous support cloth; the charged groups of the charged polymers are distributed in three layers, the ion exchange groups of the middle main layer are pyridine-type positively charged groups, and the ion exchange groups of the surface layers on both sides are sulfonate-type negatively charged groups.
Citation Information
Patent Citations
Pyridine onium salt polymer anion exchange film and preparation method thereof
CN102945975A
Method for preparing anion exchange membrane based on allyl monomer
CN103755988A